Orientation of the Eruption Fissures Controlled by a Shallow Magma Chamber in Miyakejima - Geshi, Nobuo; Oikawa, Teruki (Frontiers in Earth Science, 2016)
Orientation of the eruption fissures and composition of the lavas of the Miyakejima volcano indicate tectonic influence of a shallow magma chamber on the distribution of eruption fissures. We examined the distributions and magmatic compositions of 23 fissures that formed within the last 2800 years, based on a field survey and a new dataset of 14C ages. The dominant orientation of the eruption fissures in the central portion of the volcano was found to be NE-SW, which is perpendicular to the direction of regional maximum horizontal compressive stress (σHmax). Magmas that show evidences of magma mixing between basaltic and andesitic magmas erupted mainly from the eruption fissures with a higher offset angle from the regional σHmax direction. The presence of a shallow dike-shaped magma chamber controls the distribution of the eruption fissures. The injection of basaltic magma into the shallow andesitic magma chamber caused the temporal rise of internal magmatic pressure in the shallow magma chamber. Dikes extending from the andesitic magma chamber intrude along the local compressive stress field which is generated by the internal excess pressure of the andesitic magma chamber. As the result, the eruption fissures trend parallel to the elongation direction of the shallow magma chamber. Injection of basaltic magma into the shallow andesitic magma chamber caused the magma mixing. Some basaltic dikes from the deep-seated magma chamber reach the ground surface without intersection with the andesitic magma chamber. The patterns of the eruption fissures can be modified in the future as was observed in the case of the destruction of the shallow magma chamber during the 2000 AD eruption.